Grants recipients: ERASMUS+ program grant worth RM656,500.00 - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
Researchers from the Textile Research Group had successfully obtained an ERASMUS+ grant from European Union in January 2020. Their project is entitled “Smart Textiles-Modernization of the Curriculum of Textile Engineering and Textile Technology in Indonesia, Malaysia, and Pakistan”. The duration of this project is for 3 years starting from 15 January 2020 until 14 January 2023 with a total grant of RM 627,940.00 (EUR 135,670.00). The UiTM team is led by Associate Prof. Ts. Dr. Mohd Rozi Ahmad. Other team members are Associate Prof. Dr. Mohamad Faizul Yahya, Ts. Dr. Nor Dalila Nor Affandi, Dr. Atiyyah Musa and Ts. Dr. Wan Syazehan Ruznan.